Nitrogen Fixing Potential of Endophytic Bacteria Isolated from Aloe barbadensis Miller and Aloe sp. (Microbiology Indonesia, 2016)
Aloe is a crassulacean acid metabolism (CAM) species that are known to live in extreme enviroment such as drought condition. Nitrogen fixation procces influenced by the ability of plants to adapt in drought condition. Endophytic bacteria from Aloe and their ability for nitrogen fixation were little reported, but potential and its relationship between the ability for nitrogen fixing with resistance to drought conditions have not been reported. This research aimed study the endophytic bacteria from two varieties of aloe, namely Aloe barbadensis Miller and Aloe sp. in their ability on conducting the nitrogen fixing process and its relationship with resistance to drought. Characterization of endophytic bacteria were carried out by morphological observation of colony, Gram staining and molecular identification. Screening of nitrogen fixation was done using nitrogen-free semisolid NFb malate medium. Endophytic bacteria from Aloe sp. more than A. barbadensis in their potency of nitrogen fixation which related with habitat where their planted. A total of 40% of the endophytic bacteria isolates from the leaves of the aloe var. A. barbadensis and 62.5% of isolates from var. Aloe sp. are known to have a better ability to fixing nitrogen than the others. Isolates A barbadensis AB 12 and Aloe sp. AS 8 were the best isolates from each varieties on ability for nitrogen fixation. Based on 16S rRNA gene analysis those two selected isolates belonged to Bacillus methalotropicus strain DA 16-5 and Bacillus aryabhattai strain B8W22.Â